PENGARUH SISTEM PENGUKURAN KINERJA NON-FINANSIAL TERHADAP KINERJA ANGGOTA KEPOLISIAN, JOB TENSION SEBAGAI FAKTOR PEMEDIASI - Sri Mawarni (Akuntabilitas, 2015)
This research aims to explain the effect of non-financial performancemeasurement system, job tension, on peformance of members of the police. In order toachieve the objective of the study, this research is conducted at the police institution inLampung Province. Based on 160 usable data, we analyzed using Structural Equation Model,in particularly SmartPLS. The result of the study indicates that non-financial performancemeasurement enable to decrease job tension that it will impact on the improvement ofindividual performance. However, based on further examination whether direct or indirect ismore effective to improve a member of police performance, we found that direct relationshipbetween Non-Financial Performance Measurement System and Employee Performance ratherthan indirect effect through job tension. This study implies that non-financial performance measurement can improve the member of police institution performance.DOI: 10.15408/akt.v8i2.2766